International Tensions and Legal Disputes: Indonesia’s Aggressive Measures Against Unregulated Foreign Fishing Activities - Amarta Yasyhini Ilka Haque; Nadya Puteri Andreza; Mohd Faiz; Zahidah Abdullah (Unnes Law Journal, 2025)
This paper explores Indonesia’s aggressive measures against illegal, unreported, and unregulated fishing (IUUF) by foreign vessels in its territorial waters, a strategy that has triggered significant international tensions and legal disputes. Given Indonesia’s vast marine resources, the country has become a prime target for foreign exploitation, exacerbating the IUUF issue. The primary objective of this study is to critically assess whether Indonesia's law enforcement, particularly its policy of sinking foreign vessels engaged in illicit fishing, complies with both national and international legal standards. Through normative and qualitative research, the paper examines the legal foundation of Indonesia’s actions under Law No. 45 of 2009, and the relevant provisions of the 1982 United Nations Convention on the Law of the Sea (UNCLOS), which grants coastal states the authority to enforce their regulations and apply criminal law against foreign vessels involved in unlawful fishing within their territorial waters. The findings reveal that Indonesia’s vessel-sinking strategy is legally grounded, but it has sparked significant controversy. While domestic support for these measures has been strong, neighboring countries and international bodies have expressed concerns over the approach, leading to diplomatic challenges. This paper contributes to the broader discourse by analyzing the complex intersection of national sovereignty, international law, and marine resource management. It sheds light on the legal and political ramifications of Indonesia’s enforcement actions, enriching the ongoing debate about the rights of coastal states and the management of global marine resources.